Perancangan Visual Media Promosi Air Minum Nano Hexagonal Alkakua - Chandra, Edy; Jesslyn, Jessica (LPPM STIKI Malang, 2025)
Bottled drinking water (AMDK) is an essential commodity widely consumed by modern society. Alkakua is an AMDK product utilizing nano-hexagonal technology aimed at enhancing body health. However, the brand faces challenges in communicating its benefits and raising public awareness. This study aims to design a visual promotional media strategy for Alkakua to increase awareness among young adults aged 20-26. This research employs a qualitative descriptive approach, utilizing data collection techniques such as interviews, observations, and literature studies. The findings indicate that an effective promotional strategy for Alkakua involves printed media designs such as posters, banners, display racks, and merchandise, employing visually engaging and communicative approaches. A well-crafted visual design that aligns with brand identity and color psychology plays a crucial role in attracting the target audience's attention.